Optimal Equity Stakes and Corporate Control - Mathews, Richmond D. (Review of Financial Studies, 2007)
I show that firms may optimally sell blocks of their own equity to other firms in anticipation of future corporate control activity. In the model, a target and one potential acquirer, who may also be an alliance partner, can negotiate before synergy values are learned. I find that equity implements an optimal mechanism, allowing the partners to extract surplus from outside bidders who may arrive later. The stake is limited by the outsiders' willingness to investigate. The results imply that corporate control may motivate an equity sale even when no takeover activity is apparent at the time or occurs ex post.